The search for democratic renewal : the politics of consultation in Britain and Australia - Manwaring, Rob (Manchester Political Studies, 2014)
Why is the search for democratic renewal so elusive? This book examines both the political and policy implications of efforts by the centre-left to transform democracy. This is a story not only about democratic change, but also the identity crisis of centre-left political parties.